In Situ Phytoremediation of Mine Tailings with High Concentrations of Cadmium and Lead Using Dodonaea viscosa (Sapindaceae) - Luis Fernando Acosta-Núñez; Patricia Mussali-Galante; María Luisa Castrejón-Godínez; Alexis Rodríguez-Solís; Joel Daniel Castañeda-Espinoza; Efraín Tovar-Sánchez (Plants)
The waste generated during metal mining activities contains mixtures of heavy metals (HM) that are not biodegradable and can accumulate in the surrounding biota, increasing risk to human and environmental health. Plant species with the capacity to grow and develop on mine tailings can be used as a model system in phytoremediation studies. Dodonaea viscosa (L.) Jacq. is a shrub with wide geographical distribution and the ability to establish itself in mine tailings. The Sierra de Huautla Biosphere Reserve in Mexico contains a metallurgic district where mining activities have generated 780 million kg of waste with large concentrations of toxic heavy metals, mainly cadmium and lead. The present study evaluated the phytoremediation potential of D. viscosa in in situ conditions on soils contaminated with HMs (exposed) and reference sites (non-exposed) for one year. Also, the effects of cadmium (Cd) and lead (Pb) exposure in D. viscosa were analyzed via DNA damage (comet assay) morphological and physiological characters in exposed vs non-exposed individuals. The concentration of Cd and Pb was measured through atomic absorption spectrophotometry in the roots and leaves of plants. In total, 120 D. viscosa individuals were established, 60 growing in exposed and 60 in non-exposed soils. Exposed individuals of D. viscosa hyperaccumulated Cd and Pb in roots and leaves. At the end of the experiment, eight out of twelve characters under evaluation decreased significantly in HM-exposed plants in relation to individuals growing in non-exposed soils, except for stomatal index, stomatal coverage, and fresh leaf biomass. The micro-morphological and physiological traits of D. viscosa were not influenced by Cd and Pb bioaccumulation. In contrast, the bioaccumulation of Cd and Pb significantly influenced the macro-morphological characters and genetic damage; this last biomarker was 3.2 times higher in plants growing in exposed sites. The bioconcentration factor (BCF) of Cd and Pb in root and leaf tissue increased significantly over time. The mean BCF in root and leaf tissue was higher for Pb (877.58 and 798.77) than for Cd (50.86 and 23.02). After 12 months of exposure, D. viscosa individuals growing on mine tailing substrate showed that the total HM phytoextraction capacity was 7.56 kg∙ha−1 for Pb and 0.307 kg∙ha−1 for Cd. D. viscosa shows potential for phytoremediation of soils contaminated with Cd and Pb, given its capacity for establishing and developing naturally in contaminated soils with HM. Along with its bioaccumulation, biomass production, abundance, and high levels of bioconcentration factors, but without affecting plant development and not registering associated herbivores, it may incorporate HM into the trophic chain.